The english institute of sport`s mental health journey - Cumming, S.; Ranson, C. (British Journal of Sports Medicine, 2021)
Background Following a number of reviews into Olympic and Paralympic sport in the UK it was identified that mental health would be an area of focus for the Tokyo cycle. This led to development and implementation of a specific mental health strategy consisting of four pillars; education, provision, communication and assurance.